Karakteristik Sifat Mekanis Dan Fisik Tanah Lunak Di Kabupaten Siak Berdasarkan Pengujian Dokenbo Dan Vane Shear - Arifan Farhan; Muhamad Yusa; Ferry Fatnanta (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Soft to very soil is widely encountered in Siak Regency. Physical and mechanical properties of soft soil is very important in the construction. This research was an attempt to characterize the soil properties using portable tools namely, Dokenbo and vane shear. Dokenbo is a in-situ soil testing tool which was recently developed by the Public Works Research Institute in Japan. The Parameterswhich were obtained from the Dokenbo test includes the value of penetration, torque (T0), and the shear angle in the soil (Ø). Vane Shear test was conducted to obtain undrained shear strength in the field. The purpose of this study is to obtain a simple relationship (correlation) between the mechanical properties of using Dokenbo and Vane Shear, and the correlation between mechanicalproperties and soil physical properties. Vane Shear and Dokenbo was used to obtain mechanical properties while physical properties were obtained from laboratory testing. The results then were analyzed using linear regression. The results of the Dokenbo test in this study includes the penetrationvalue in the range from 418 to 1373 kN/m2, the torque value (T0) in the range from 0,3 to 0,65 N.m, and the internal shear angle (Ø) was in the 24o to 60o range. Soil shear strength value from vane shear test results range from 6 to 64 kPa. From the test results obtained, the correlation betweenpenetration and shear strength (Su) has a very strong interpretation, likewise is the correlation between the correlation (T0) and Su. The internal shear angle (Ø) correlation and Su shows no correlation. Meanwhile, the correlation between mechanical properties and soil physical properties has a moderate correlation.Keywords: Dokenbo, Shear Strength, Penetration, Torque, Inner Shear Angle